1994
DOI: 10.1073/pnas.91.6.2315
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of tyrosine phosphatase and inhibition of cell proliferation by somatostatin analogues: mediation by human somatostatin receptor subtypes SSTR1 and SSTR2.

Abstract: The effects of s analgus RC-160and SMS-201-995 on tyrosine phosphatase and cell proliferation were investigated in COS-7 and NIH 3T3 cells expressing human somatostatin receptor subtype 1 or 2 (SSTR1 or SSTR2 antagonize the mitogenic effect of growth factors acting on tyrosine kinase receptors such as epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) (9-11). Furthermore, these analogues have been found to stimulate tyrosine phosphatase activity in normal and tumoral pancreatic cells (9,(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
208
0
8

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(227 citation statements)
references
References 27 publications
9
208
0
8
Order By: Relevance
“…11 We therefore investigated whether sst2 induces cell death in this previously described and characterized model. 11,12 We quantified apoptosis by using the terminal deoxynucleotidyltransferase (TdT)-mediated dUTP-biotin nick end labeling (TUNEL) technique. After 5-h cell serum starvation, apoptosis in sst2-expressing cells was 3.6-71.2-fold higher than in mock cells (5.670.8 versus 1.570.5% of apoptotic cells, respectively) ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We therefore investigated whether sst2 induces cell death in this previously described and characterized model. 11,12 We quantified apoptosis by using the terminal deoxynucleotidyltransferase (TdT)-mediated dUTP-biotin nick end labeling (TUNEL) technique. After 5-h cell serum starvation, apoptosis in sst2-expressing cells was 3.6-71.2-fold higher than in mock cells (5.670.8 versus 1.570.5% of apoptotic cells, respectively) ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Murine fibroblastic NIH3T3 cells were transfected either with the human 1.35-kbp sst2 cDNA (NIH3T3/sst2 cells (clone 2/5 11 ), NIH3T3/sst2.1 cells (clone 2/1 11 )), or with the mock vector (mock cells), and cultured as previously described. 11,12 Cells were treated with 10 ng/ml TNFa (Preprotech Inc.) in the presence of 10 mg/ml of cycloheximide (Sigma). For experiments involving specific inhibitors, cells were pretreated for 1 h with 10 mM DEVD-CHO or IETD-CHO (BIOMOL), 25 mg/ml SN50 or SN50M (SN50Mutated) (BIOMOL), 10 mM Helenalin (BIOMOL), 10 mM SP600125 (BIOMOL), or with 10-50-100 nM BIM23627 (Biomeasure).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular events leading to the inhibition of cell proliferation are still poorly understood, it has been shown that, after binding to somatostatin receptors, somatostatin analogues cause a rapid stimulation of a membrane proteintyrosine phosphatase (PTPase) 1 activity and dephosphorylate phosphorylated epidermal growth factor receptors (9,11,12) suggesting that a PTPase may participate in the somatostatininduced inhibition of growth factor-mediated mitogenic signal. Recently, the expression of the sst2 somatostatin receptor subtype in NIH3T3 and Chinese hamster ovary (CHO) cells led us to the demonstration of the direct involvement of sst2 in both the antiproliferative effect of somatostatin and its stimulatory effect on PTPase activity (13,14). Incubation of cells expressing sst2 with the PTPase inhibitor, vanadate, prevented both effects suggesting that a PTPase may be implicated in the negative growth signal induced by activation of sst2.…”
mentioning
confidence: 99%
“…All appear to be linked to the inhibition of adenyl cyclase (Patel et al, 1994), but this pathway does not appear to be of primary importance in the antiproliferative activity of somatostatin. Both hSSTR2 and hSSTR1 exhibit growthinhibitory effects via tyrosine phosphatases in vitro (Leibow et al, 1989;Todisco et al, 1994;Buscail et al, 1994) and, hence, can directly antagonize the effects of growth factors, such as EGF (Vidal et al, 1994). hSSTR5 is also linked to the inhibition of proliferation in vitro, although the mechanism appears to be the inhibition of intracellular calcium mobilization (Buscail et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin was initially isolated as a growth hormone release-inhibiting factor and has subsequently been found to be a pan-inhibitory peptide, which inhibits proliferation in a wide variety of cell types, even following malignant transformation (Patel et al, 1981). There is evidence that this antiproliferative activity may be caused by a number of mechanisms, including inhibition of release of stimulatory systemic hormones and growth factors (Patel et al, 1981), inhibition of angiogenesis (Woltering et al, 1990), immunomodulation (Partsch et al, 1992) and direct action through high-affinity, cell-surface receptors (Pagliacci et al, 1991;Buscail et al, 1994). Five highaffinity, cell-surface somatostatin receptors of the seven-transmembrane, G-protein-coupled type have been identified and their genes sequenced (Yamada et al, 1992a(Yamada et al, , b, 1993Rohrer et al, 1993;O'Carroll et al, 1993).…”
mentioning
confidence: 99%